Assessment of disease activity in systemic vasculitis. Issue 867 (January 1998) - Tse, W. Y.; Cockwell, P.; Savage, C. O.
Abstract : The systemic vasculitides are a group of inflammatory disorders characterised by relapses and remission. Before the introduction of immunosuppressive drugs, mortality was unacceptably high. Immunosuppressive therapy has had a therapeutic impact, but at the cost of increased risk of infection and other adverse effects. Differentiating infection from active disease can be difficult, and the inappropriate prescription of immunosuppressive drugs can be fatal. Hence disease indices which can aid physicians to identify the active phase of disease and enable early treatment, will be valuable in the management of this group of disorders.